Ending wars, consolidating peace economic perspectives - Berdal, Mats; Wennmann, Achim (Adelphi Series : International Institute for Strategic Studies), 2010)
"This Adelphi offers a series of economic perspectives on conflict resolution, showing how the challenges of peacebuilding can be more effectively tackled. From the need to marry diplomatic peacemaking with development efforts, and activate the private sector in the service of peacebuilding aims, to the use of taxes and natural- resource revenues as a financial base for sustainable peace, this book considers how economic factors can positively shape and drive peace processes. It examines the complex ways in which power and order may be manifested in conflict zones, where unpalatable compromises with local warlords can often be the first step towards a more lasting settlement. In distilling expertise from a range of disciplines, this Adelphi seeks to inform a more economically integrated and responsive approach to helping countries leave behind their troubled pasts and take a fuller role in constructing their futures."--Back cover